Критерії визначення розміру компенсації моральної шкоди - Тетяна Кочірко (Видавництво Львівської політехніки, 2013)
The article analyses current issues in defining the criteria for moral damage compensation and the moral damage institution role for the human rights and freedoms protection. Moral damage compensation as the way of human rights protection is one of the most important institutions in the modern law sciences. The need to establish clear criteria for determining moral damage compensation is urgent, because the current criteria approach is very general with no much sence and is far from being perfect. The right to moral damage compensation is very important, because people have always asserted their right to dignity and the legal protection of it through the moral damage compensation is necessary in our society.
Keywords: моральна шкода; право людини; компенсація; критерії; наукові підходи